FINANCIAL MANAGEMENT OF ENTREPRENEURIAL UNIVERSITIES IN THE CONDITIONS OF DIGITALIZATION, SMART ECONOMY AND THE DEVELOPMENT OF EDUCATIONAL TOURISM - Oleksandr Galych; Marta Barna; Oleg Fedirets; Hanna Fedirko; Taliat Bielialov; Polina Puzyryova (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article defines the key aspects of methodical support of financial management of entrepreneurial universities in the conditions of digitalization, smart economy and development of educational tourism. Attention is focused on the fact that at this time Ukraine faced complex phenomena caused by the invasion of the Russian Federation on the territory of our state, which caused powerful changes in all sectors, industries and industries of Ukraine. It was noted that against the background of active digitalization and financial instability, migration shifts and the flow of human resources took place. In this context, there is a need for an active policy of creating and evaluating the effectiveness of the concept of financial management of entrepreneurial universities in the conditions of digitalization, smart economy and the development of educational tourism, taking into account the challenges faced by the modern economy of Ukraine. With the use of methods of production functions, the article proposes an assessment of the financial management of entrepreneurial universities. It was noted a need to increase the financial support of entrepreneurial universities, which is important for improving the quality of education and tax revenues at the regional and state levels. Attention is focused on the phenomenon of increased outflow of students outside of Ukraine with the simultaneous outflow of teaching staff abroad. It was noted that it is the effective financial policy of supporting entrepreneurial universities that can reduce negative phenomena in education.